Trends in Implementation of Problem-Based Learning with Flashcard Media in Improving Elementary Students Mathematical Abilities: A Systematic Literature Review - Lutfi'ah Sungkar; Decky Avrilianda; Bambang Subali; Nuni Widiarti (FKIP - Universitas Riau, 2026)
Mathematics learning in elementary schools often faces obstacles due to the abstract nature of the material, which is difficult for students in the concrete operational stage to understand. This condition requires learning models and learning media that can bridge abstract concepts to make them more tangible and easier to understand. This review aims to examine trends in problem-based learning models and flashcard media in mathematics learning in elementary schools during the period 2020–2025. The research methods used are a systematic literature review with bibliometric analysis. Data were collected through the Publish or Perish (POP8) application connected to Google Scholar. The search yielded 210 articles, which were then selected based on inclusion and exclusion criteria, leaving 25 articles relevant for analysis. The results of the analysis showed that the problem-based learning model and flashcards in mathematics learning in elementary schools experienced a significant increase in the 2020–2025 period. Overall, the problem-based learning model and flashcards proved to be effective in increasing student motivation, engagement, and understanding of mathematical concepts. This study provides a comprehensive overview of the direction and potential for creative, interactive, and relevant research for mathematics learning in elementary schools.